The Intersection of Criminal Law, Technology and Business Commercial Law on Carding as Cyber Fraud - Ridwan Arifin; Hartini Atikasari; Waspiah Waspiah (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: Â Since digital reform, business and trade sectors have begun to expand their network in cyberspace. Transactions carried out also no longer refer to ordinary things. The modern era of society indeed prefers a more efficient payment process, namely through a credit card. On the other hand, the advancement of digital technology also provides opportunities for perpetrators of crime in cyberspace. The fraud, which was initially carried out with the objects of written reports, began to move lanes towards data manipulation in the form of carding.Purpose/Objective Study: This paper is intended to analyze and examine carding as cyber fraud in three legal studies: criminal law, business, and commercial law, and transnational criminal law. This study illuminates the intersection between criminal law, business and commercial law, law and technology, and international criminal law in carding cases.Design/Methodology/Approach: The paper is normative legal research using a comparative approach and regulations related to carding and cyber fraud.Findings: The study highlighted that carding as a manifestation of cyber fraud is also a transnational crime, which involves networks or groups across national borders to carry out certain illegal businesses or activities. Included in this case is the data theft on credit cards. Of course, this has resulted in a shift of public trust towards the credit card provider sector, namely banks, so that there is a need to strengthen the juridical pathway nationally and internationally.Paper Type: General Review